Artillery officer education and the interoperability challenge in Joint fires: a Czech–Slovak comparison - Michal Šustr; Michal Vajda; Martin Blaha; Jan Ivan; Daniel Korec (Cogent Education)
Interoperability remains a fundamental requirement within NATO, enabling effective coordination and cooperation during joint operations among allied forces. This article focuses on a comparative analysis of the university-level education of artillery officers in the Czech Republic and Slovakia, examining the structure of curricula, duration of study and variations in professional specialization. Based on the findings, the paper proposes a unified educational model that integrates branch-specific competencies with standardized technical, tactical and operational training. The proposed framework aligns with NATO standards and addresses the demands of the contemporary battlespace, incorporating operational insights from the ongoing Russia–Ukraine conflict. Furthermore, the model introduces shared training modules aimed at significantly enhancing the interoperability of allied artillery forces. The comparative analysis revealed differences in instructional hours, the extent of practical training and the integration of modern teaching methods, all of which influence the preparedness of officers. The findings demonstrate that current disparities may limit the ability to conduct joint fire support in multi-domain operations, making the proposed unified curriculum a crucial step toward enhancing alliance interoperability.